Locally emitted fungal spores serve as high-temperature ice nucleating particles in the European sub-Arctic - Gratzl, Jürgen; Böhmländer, Alexander; Pätsi, Sanna; Pogner, Clara-E.; Gorfer, Markus; Brus, David; Doulgeris, Konstantinos Matthaios; Wieland, Florian; Asmi, Eija; Saarto, Annika; Möhler, Ottmar; Stolzenburg, Dominik; et al. (Copernicus Publications, 2026)
Primary biological aerosol particles (PBAPs) can influence weather and climate by acting as high-temperature ice nucleating particles (INPs), especially in clean, rural regions like the European sub-Arctic. However, the actual contribution to atmospheric ice nucleation and the exact identity of PBAPs serving as INPs remain poorly understood.
Here, we present measurements of INPs and highly fluorescent aerosol particles (HFAPs) over the course of 1 year at the Pallas Atmosphere-Ecosystem Supersite in the Finnish sub-Arctic, aiming to determine whether PBAPs significantly contribute to atmospheric INPs and to identify which types do so. Our findings indicate that certain HFAPs are strongly influenced by meteorological variables, with high concentrations occurring when the station is within the atmospheric mixing layer, suggesting local biological sources. These HFAPs are the main contributors to high-temperature INPs, with an exceptionally strong correlation (r = 0.94, p < 0.0001) between HFAP concentrations and INPs active at -13.5 degrees C. For the first time, to the best of our knowledge, we combine INP and HFAP data with direct fungal spore counts and environmental DNA (eDNA) analysis to determine the biological origins of HFAPs and INPs. The results suggest that most high-temperature INPs are likely fungal spores. eDNA analysis further reveals that airborne fungi are dominated by Basidiomycota and that only a small fraction of the detected fungal genera have, to date, been tested for ice nucleation activity (INA) according to the literature. Among those reported in the literature, most exhibit very low or no INA. This underscores the significant knowledge gap in our understanding of biological ice nucleation in the atmosphere.